Management of ureteral endometriosis with hydronephrosis: Experience from a tertiary medical center. Issue 10 (14th July 2017) - Huang, Jing‐Zhi; Guo, Hong‐Ling; Li, Jin‐Bo; Chen, Shu‐Qin
Abstract: Aim: We report the clinical characteristics and experience of the surgical management of ureteral endometriosis in our institution. Methods: We retrospectively reviewed the data of patients with hydronephrosis resulting from ureteral endometriosis. Results: Forty‐six patients with different degrees of hydronephrosis were included in the study; 35% had urinary tract symptoms. Concomitant involvement of the ipsilateral ovary occurred in more than two‐thirds of the patients. Four patients had nephrectomy, one of which involved ureterolysis because of hydronephrosis recurrence six months later. Conclusions: Hydronephrosis may be caused by uncommon reasons, such as ureteral endometriosis, which can even cause silent loss of renal function. Routine ultrasound scanning of the upper urinary tract for severe stages of endometriosis is very important in order to detect any potential ureteral lesions. Ureterolysis should be considered as the first surgical step, not only to avoid iatrogenic ureteral injuries but also to better evaluate ureter involvement for further procedures. To warrant tension‐free and lesion‐free anastomosis, it is wise to perform ureteroneocystostomy for long‐term sound results.